The economic crisis in Greece and policy for its overcoming - Kundera, Jarosław (Economics of the 21st Century, 2015)
The crisis of the euro area is undoubtedly a continuation of the global crisis that started on the real estate market in the USA, and from there spread to Europe, touching Greek economy the hardest. The purpose of this article is the analysis of causes of economic crisis in Greece and to determine high performance methods to its overcoming. To develop effective methods to combat the crisis and prevent future breakdowns changes must cover not only Greek economic policy, but also a mechanism for international cooperation. The crisis of the euro area turned out to be not only a crisis of the economies of member countries, but also of the mechanism of integration. It is especially about the economic policy carried out at the level of the EU institutions that affects the economic policies of individual member countries. Hence the article tries to find an answer to the question, what changes should be made in Greek economic policy as well as in the EU institutional framework to overcome the present crisis and to prevent its occurrence in the future. A permanent solution of the crisis can be only a transformation of Greek economy that was most acutely affected by a decline in production and an increase in unemployment
Ekonomia XXI Wieku = Economics of the 21st Century, 2015, Nr 4 (8), s. 47-73
Keywords: economic transformation; growth of export; unemployment in Greece; structural policy; public debt in Greece; budget deficit in Greece; banking reforms; ekonomiczna transformacja; wzrost eksportu; bezrobocie w Grecji; polityka strukturalna; reforma bankowa